Vitamin D3-upregulated protein 1 (VDUP1), a crucial regulator of the redox equilibrium, controls aging of Drosophila - Bajorat, Jörg (2016)
Aging of higher organisms is a complex biological process characterized by progressive deterioration of cellular functions and a higher risk to die within a given time period. Age-related loss of cellular functions can be attributed to damage of macromolecules like DNA, proteins and lipids. In the “free radical theory of aging” Denham Harman claimed that reactive oxygen species (ROS) arising from normal metabolic processes are responsible for accumulation of damage and, therefore, represent the main cause of aging. Thioredoxin-interacting protein (TXNIP) has been described as a negative regulator of the cellular redox equilibrium, which is attributed to functional inhibition of thioredoxin (Trx). TXNIP overexpression leads to an increased sensitivity towards oxidative damage. In humans, TXNIP was shown to be expressed in an age-dependent manner in various tissues including T cells, hepatocytes and hematopoietic stem cells. To elucidate the underlying mechanism of TXNIP-induced disturbance of the cellular redox equilibrium a Drosophila model was established. For this purpose, Schneider S2 cells were used as an in vitro model to overexpress the Drosophila TXNIP homologue vitamin D3-upregulated protein 1 (VDUP1). In this thesis, I show that VDUP1 overexpression leads to increased basal ROS levels and, thus, to a higher sensitivity towards oxidative stress. In addition, to investigate a potential effect of VDUP1 on aging in an in vivo model, VDUP1-overexpressing and VDUP1 knockdown flies were generated. High expression of VDUP1 in flies is correlated to a lower resistance to oxidative stress and to a shortened lifespan. Upon VDUP1 knockdown, female flies show a prolonged healthy lifespan in conjunction with an increased oxidative stress resistance. Taken together, experiments performed in this thesis characterize VDUP1 as an essential regulator in joining oxidative stress resistance to lifespan regulation in Drosophila.
Die Ziffer "3" im Titel ist tiefgestellt
Keywords: Hochschulschrift